Modelo administrativo y financiero para la finca agrícola “Sevilla”. - Torres Rivera, Denis Madelei (2017)
The objective of the present research was to Design a Financial Administrative Model for the "Sevilla" Agricultural Farm. The main reason for this project was to help solve the different problems faced by the Farm and to obtain a greater competitiveness in its activities. which was necessary to define an administrative manual and the formats of accounting-financial records that facilitate the correct and orderly management of the financial administrative system. Being a type of descriptive and applied research, the inductive and analytical methods were used for the development of the same, all this supported in primary and secondary sources that allowed the collection of data objects of studies. The work began with a description of the current situation of Finca, through the application of surveys conducted to employees. Achieving the necessary information to meet the proposed objectives, data that were tabulated and confronted by percentage relation with the help of Excel. From the results obtained in the application of the surveys, it was observed that the highest percentage of respondents stated that the farm does not currently have adequate administrative management, due to problems of coordination of activities and the management of staff is very poor as well as the different processes that are carried out. It was evidenced that the inadequate organization in the administrative area causes problems and does not consider important organizational administrative aspects for the improvement and performance of activities such as: specific areas, levels of hierarchy and responsibility, and the establishment of functions according to the jobs. The analysis of results determined the importance of having a financial administrative manual, the lack of records in which a control of expenses can be carried out. Key words: Manual, Administrative, Financial, Organization.